High-resolution bacterial 16S rRNA gene profile meta-analysis and biofilm status reveal common colorectal cancer consortia - Drewes, J.L.; White, J.R.; Dejea, C.M.; Fathi, P.; Iyadorai, T.; Vadivelu, J.; Roslani, A.C.; Wick, E.C.; Mongodin, E.F.; Loke, M.F.; Thulasi, K.; Gan, H.M.; et al. (Nature Publishing Group, 2017)
Colorectal cancer (CRC) remains the third most common cancer worldwide, with a growing incidence among young adults. Multiple studies have presented associations between the gut microbiome and CRC, suggesting a link with cancer risk. Although CRC microbiome studies continue to profile larger patient cohorts with increasingly economical and rapid DNA sequencing platforms, few common associations with CRC have been identified, in part due to limitations in taxonomic resolution and differences in analysis methodologies. Complementing these taxonomic studies is the newly recognized phenomenon that bacterial organization into biofilm structures in the mucus layer of the gut is a consistent feature of right-sided (proximal), but not left-sided (distal) colorectal cancer. In the present study, we performed 16S rRNA gene amplicon sequencing and biofilm quantification in a new cohort of patients from Malaysia, followed by a meta-analysis of eleven additional publicly available data sets on stool and tissue-based CRC microbiota using Resphera Insight, a high-resolution analytical tool for species-level characterization. Results from the Malaysian cohort and the expanded meta-analysis confirm that CRC tissues are enriched for invasive biofilms (particularly on right-sided tumors), a symbiont with capacity for tumorigenesis (Bacteroides fragilis), and oral pathogens including Fusobacterium nucleatum, Parvimonas micra, and Peptostreptococcus stomatis. Considered in aggregate, species from the Human Oral Microbiome Database are highly enriched in CRC. Although no detected microbial feature was universally present, their substantial overlap and combined prevalence supports a role for the gut microbiota in a significant percentage (>80%) of CRC cases.